Price Changes in Regulated Healthcare Markets: Do Public Hospitals Respond and How? - Rossella Verzulli; Gianluca Fiorentini; Matteo Lippi Bruni; Cristina Ugolini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper examines the behaviour of public hospitals in response to the average payment incentives created by price changes for patients classified in different Diagnosis Related Groups (DRGs). Using panel data on public hospitals located within the Italian region of Emilia-Romagna, we test whether a one-year increase in DRG prices induced public hospitals to increase their volume of activity, and whether a potential response is associated with changes in waiting times and/or length of stay. We find that public hospitals reacted to the policy change by increasing the number of patients with surgical treatments. This effect was smaller in the two years after the policy change than in later years, and for providers with a lower excess capacity in the pre-policy period, whereas it did not vary significantly across hospitals according to their degree of financial and administrative autonomy. For patients with medical DRGs, instead, there appeared to be no effect on inpatient volumes. Our estimates also suggest that an increase in DRG prices either decreased or had no impact on the proportion of patients waiting more than six months. Finally, we find no evidence of a significant effect on patients' average length of stay.
Keywords: I11; I12; I18; 330